In-hospital mortality and length of stay among patients with infective endocarditis and solid organ transplant: A study from National Inpatient Sample 2016–2019. Issue 6 (June 2022) - Baral, Nischit; Volgman, Annabelle Santos; Gupta, Tripti; Kunadi, Arvind; Khan, Mahin R.; Kambalapalli, Soumya; Changezi, Hameem U.; Tracy, Melissa
Abstract: Infective endocarditis (IE) is a rare but serious complication following a Solid Organ Transplant (SOT). Due to the lack of sufficient studies, we aimed to compare in-hospital mortality and length of stay (LOS) of patients primarily admitted for IE (index or principal hospitalization) with history of SOT, including the subgroup of heart or lung transplant (HLT), to those without a history of SOT (non-SOT) or HLT (non-HLT). We used the 2016–2019 National Inpatient Sample, the largest all-payer inpatient hospital data from Healthcare Cost and Utilization Project (HCUP), including patients 18 years or older with IE, as a principal diagnosis for hospitalization. From 2016 to 2019, there were 56, 330 principal or index hospitalizations for IE. Among them, 0.6 % (n = 327) were SOT recipients, 0.1% (n = 68) were HLT recipients, and 41.4% were females. The mean age was 51.9 ± 19.2 years. Compared to non-SOT controls, SOT recipients were older (mean age 59.3 vs. 51.8 years; P = 0.002) and had higher Charlson-comorbidity-index (CCI) of 3 or more (87.7% vs. 33.2%; p < 0.001). SOT status was not statistically significant for a higher or lower odds of in-hospital mortality (adjusted odds ratio (aOR) 0.7; 95% confidence interval (CI): 0.2, 2.4; p = 0.60) or increased or decreased LOS (coefficient: -0.1, 95% CI: -0.4, 0.1; p = 0.23) among index IE hospitalizations after controlling for age, sex, race, hospital-region, hospital-teaching status, income, insurance status, and CCI. HLT status was also not associated with higher or lower odds of in-hospital mortality (aOR 1.4; 95% CI: 0.2, 13.1; p = 0.77) or increased or decreased LOS (coefficient: -0.1, 95% CI: -0.3, 0.5; p = 0.59). From 2016 to 2019, the rate of index IE hospitalization trends from 37.8 to 41.4 per 100, 000 overall hospitalizations (p = 0.001). We found the rate of index IE hospitalizations increasing with time. Among index IE hospitalizations, SOT, including a subgroup of HLT recipients, have similar in-hospital mortality and LOS compared to non-SOT or non-HLT groups. We need a larger sample size to comment on outcomes of IE hospitalizations with the HLT subgroup. Abstract : Infective endocarditis, Solid organ transplant, Heart or lung transplant, In-hospital mortality.